Finite-element thermal analysis of a new cooler design - Lazić, Ladislav (Materiali in tehnologije, 2004)
A mathematical model of the cooling process of an octagonal cross-section steel semi-product was constructed on the basis of the finite-element analysis technique. The temperature variation throughout the structure causes thermal contraction stresses and deformations. Transient heat-conduction analyses and thermal stress analyses were performed to determine the allowable rate of cooling with regard to the temperature distribution within the structure and the stresses and deformations resulting from the variation of the heat-transfer coefficient of forced convection.
Keywords: kontinuirno litje; ohlajanje; napetosti; deformacije; matematični modeli; metoda končnih elementov; finite element method